(untitled) (Research, Society and Development, 2021)
Geotechnologies are increasingly accessible and this is due to the fact that free and free software is being progressively produced and disseminated, as well as the adequacy of the language of these software that is being demanded, in order to allow access to an increasingly broad audience. The objective is to diagnose the use of geotechnologies as an instrument of teaching Geography. The referred study was carried out in loco with 6th grade students at the public school of state Prof. Virgílio Libonati located in the metropolitan region of Belém do Pará, whose pair of coordinates for access is 01°27’9.73” South latitude and 48°26’38.22” West longitude. The methodology included the application of questionnaires after a lecture with the purpose of better understanding about cartography, the environment and computational utilities. The audience was 20 (Twenty) students in the age group of 11 years belonging to the afternoon shift. This approach highlighted the importance of geotechnogies in everyday school life, seeking to make geographic concepts more dynamic and effective during the teaching-learning process.